Sacrifice and the Homeric Hymn to Hermes 112-41 - Thomas, Oliver (Cambridge University Press, 2017)
Examines the methodology by which one can connect this passage to historical sacrificial practices. In particular, I critique the previous approaches of Kahn, Clay and Burkert, and argue that the passage can be taken as aetiological with special reference to the site at Olympia.